Organizational Resilience as An Antecedent of Efficient COVID 19 Induced Public Grant Distribution in the EU - Mate DAMIĆ (Communications of International Proceedings, 2022)
The COVID 19 pandemic was an unprecedented external shock to global markets. It led to a strong governmental response around the world. European Union countries implemented a broad financial aid program for firms affected by the pandemic. The quick policy response helped organizations cope with the new market circumstances. However, many of the COVID 19 induced public grants were indiscriminate in terms of firm eligibility. This led to questions being asked about their efficiency.  Research has shown that aid measures served as a lifeline for a number of inefficient firms that would have otherwise exited the market regardless of the pandemic. We argue that organizational resilience is the key trait that acts as an early signal of potential firm survival following the onset of an economic crisis and could be used as a criterion for estimation whether the firm should receive public grants or not. However, the question how and in which way are COVID 19 induced public grants related to organizational resilience remains unclear. The aim of this paper is to analyse relevant research findings related to this question in the EU context as well as to provide recommendations for policy makers.
Keywords: organizational resilience; COVID 19 pandemic; public grants; EU